2021
DOI: 10.21037/apm-20-2279
|View full text |Cite
|
Sign up to set email alerts
|

Lazarus type response to immunotherapy in three patients with poor performance status and locally advanced NSCLC: a case series and literature review

Abstract: Background: Immune checkpoint inhibitors (ICIs) have become the standard treatment for patients with advanced non-small cell lung cancer (NSCLC). However, the safety and efficacy of ICIs in severe advanced NSCLC patients with poor performance status (PS) are still unclear.Methods: In the current study, we report a retrospective case series of three critically ill NSCLC patients with poor PS treated with immunotherapy in our hospital, and discussed these cases with reference to the existing literature and guide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Firstly, we report cases of patients, some also terminally ill, with poor PS and critically high disease burden, with rapid improvement of patients' health conditions during the very first days of treatment. Moreover, to the best of our knowledge, the only case series of the Lazarus effect during ICIs available in the literature [12,13] reported a median time to clinical response of 6 and 5 weeks, respectively. No patients interrupted treatment due to immunotherapy-related adverse events, leading to a good quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, we report cases of patients, some also terminally ill, with poor PS and critically high disease burden, with rapid improvement of patients' health conditions during the very first days of treatment. Moreover, to the best of our knowledge, the only case series of the Lazarus effect during ICIs available in the literature [12,13] reported a median time to clinical response of 6 and 5 weeks, respectively. No patients interrupted treatment due to immunotherapy-related adverse events, leading to a good quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…A Lazarus response was also described in three patients affected by advanced non-small cell lung cancer with strong expression of PD-L1 (>50%) with a PS ECOG 4 at the treatment baseline. They were treated with immune checkpoint inhibitors and demonstrated a very rapid improvement of PS ECOG to 1 or 0 [13]; in these cases, the median time to clinical response was 5 weeks (range 1-7 weeks).…”
Section: Discussionmentioning
confidence: 99%
“…The patient received combination therapy including endoscopic recanalization of central airway followed by immunotherapy, which reduced tumor lesions and improved the PS score (180). Case reports have shown that immunotherapy was also effective in patients with a PS of 4 (181,182). Nevertheless, the role of immunotherapy in patients with poor PS scores needs to be further investigated.…”
Section: Immunotherapy (Recommendation Category: B; Level Of Evidence: 1b)mentioning
confidence: 99%
“…Improvement in PS has been seen with ICI therapy. Nie et al 10 reported that three patients at their institution with NSCLC and ECOG PS of 4 with programmed cell death ligand 1 expression of more than 50% all experienced a Lazarus-type response. Gounant et al 11 has reported that in their study of 35 consecutive patients with PS 3-4 advanced NSCLC who received compassionate use nivolumab, nine patients (approximately 26%) had a PS improvement to 0-1, which corresponded to a median overall survival of 43 months.…”
mentioning
confidence: 99%